Programas de disseminação de experiências de governos locais no Brasil em contexto de redemocratização e de descentralização - Mattos, Janaina Valéria de (2005)
This dissertation describes and analyzes the history and the way that operates five programs of dissemination about local governments experiences in Brazil. It discusses to the light of the quarrel on State Reform, in a context of decentralization of competences and redemocratization, after a military regimen. It detaches the influence of these programs in the formation of public administrators, in a general context, and the constitution of organizations net and people dedicated to the production of knowledge and search for the dissemination of local governments experiences, with the perspective and the objectives of the distinct responsible organizations for programs analyzed.